A method for TiC ceramic powder enhanced laser additive manufacturing CoCrNi medium entropy alloy
The preparation of TiC ceramic powder-enhanced CoCrNi medium-entropy alloys through mechanical ball milling and laser selection melting technology has solved the problem of defects in medium-entropy alloys in additive manufacturing, and achieved high-performance medium-entropy alloy preparation, reducing energy consumption and improving material ejaculation Density and hardness.
Patent Information
- Application Number
- CN202310680972.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-06-09
AI Technical Summary
In the entropy alloy CoCrNi in additive manufacturing, cracks and hole defects are prone to occur, which affects its performance. The traditional defect elimination method consumes high energy and takes a long time.
By selecting the CoCrNi alloy powder and TiC ceramic powder with a particle size of (10-60)μm, mechanical ball milling and vacuum drying are carried out, and TiC ceramic powder-enhancing CoCrNi medium-entropy alloy is prepared in combination with laser selection melting technology (SLM) to optimize powder mixing Scale and 3D printing parameters to reduce defects and improve performance.
Under low energy consumption, the density and Vickers hardness of the medium-entropy alloy are improved, the grains are refined, internal defects are reduced, cracks and hole defects are significantly reduced, and the mechanical properties of the material are improved.
Smart Images

Figure CN116727686B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of additive manufacturing defect elimination, and in particular to a method for TiC ceramic powder-enhanced laser additive manufacturing of a CoCrNi medium-entropy alloy. Background Art
[0002] Medium-entropy alloys are alloys composed of ternary or quaternary metal elements in equal or near atomic ratios. Studies have shown that medium-entropy alloys have better mechanical properties than high-entropy alloys and traditional alloys with five or more elements. At the same time, medium-entropy alloys also have excellent properties such as high hardness, high density, high thermal stability and high corrosion resistance. Therefore, medium-entropy alloys have great application potential in aerospace, marine equipment and other fields.
[0003] At present, there are many research reports on the ternary CoCrNi system in medium entropy alloys. The performance control methods of traditional cast medium entropy alloys mainly include changing the atomic ratio, heat treatment and rolling treatment, adding new alloying elements, etc. In addition, studies have shown that adding micron-sized solid particles to metal alloy materials can reduce the stacking fault energy of the alloy and achieve dispersion strengthening effects, thereby improving the mechanical properties of the alloy. Therefore, strengthening CoCrNi medium entropy alloys by micron ceramic particles has great research and practical significance.
[0004] At present, the preparation of medium-entropy alloys is mainly based on arc and induction melting, while advanced additive manufacturing technology, also known as 3D printing, integrates computer foundation, three-dimensional modeling, and automated control. It is a bottom-up layer-by-layer manufacturing method, which is very different from the traditional melting method. It can make the precision manufacturing of complex structures that are difficult to process with traditional melting processes a reality. Among the additive manufacturing methods, selective laser melting has a higher heating and faster cooling rate, which is conducive to inhibiting grain growth, thereby effectively improving performance. However, if the process parameters and powder system are not properly selected, defects such as cracks and pores will occur inside the material or parts during the additive manufacturing process, seriously affecting its use.
[0005] The internal defects of additively manufactured CoCrNi medium-entropy alloys are the main factors affecting their performance. Therefore, how to avoid or reduce printing defects and improve the mechanical properties of additively manufactured CoCrNi medium-entropy alloys is the main research direction of scholars at present. Different from the traditional cast medium-entropy alloys that eliminate defects and strengthen mechanical properties, adding a certain amount of micron-sized solid ceramic particles to the initial CoCrNi medium-entropy alloy powder can significantly reduce printing defects and strengthen alloy properties. In this regard, the present invention proposes a new method for reducing or eliminating internal defects and enhancing performance of additively manufactured CoCrNi medium-entropy alloys. Summary of the invention
[0006] The purpose of the present invention is to provide a method for TiC ceramic powder enhanced laser additive manufacturing CoCrNi medium entropy alloy, which solves the following technical problems:
[0007] (1) How to reduce the adverse effects of cracks and holes in entropy alloys during additive manufacturing on parts;
[0008] (2) How to achieve the goal of eliminating defects in medium-entropy alloys that consume a lot of energy and take a long time while improving the performance of medium-entropy alloys.
[0009] The purpose of the present invention can be achieved through the following technical solutions:
[0010] A method for manufacturing a CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing, the method comprising:
[0011] S1. CoCrNi alloy powder and TiC ceramic powder with a particle size of (10-60) μm are selected, and the atomic ratio of the two is CoCrNi:TiC=(0.8-1):(0.2-0), for preparing CoCrNi / TiC medium entropy alloy powder;
[0012] S2, preparing a mixed powder of CoCrNi and TiC ceramics by mechanical ball milling;
[0013] S3. The mixed powder is vacuum dried, and a TiC ceramic powder reinforced CoCrNi medium entropy alloy material with few defects and excellent performance is prepared by selective laser melting (SLM).
[0014] Preferably, the specific process of the CoCrNi / TiC entropy alloy powder in S1 is:
[0015] S2.1. Weigh the original powder components CoCrNi metal powder and TiC ceramic powder according to the calculated powder mass. The particle size of the two powders is (10-60) μm. The two alloy powders are in atomic (CoCrNi) y / TiC x It means that x+y=1;
[0016] Among them, (CoCrNi) y / TiC x Including the atomic ratios are: Alloy 1: (CoCrNi) 1; Alloy 2: (CoCrNi) 0.9 / TiC 0.1 ; Alloy 3: (CoCrNi) 0.8 / TiC 0.2 ;
[0017] S2.2, put the powder in S1.1 into a ball mill, and use a ball mill for mechanical ball milling;
[0018] S2.3. Collect the ball-milled powder in S1.2 and put it into a vacuum drying oven for drying at a temperature of 68 to 72° C. for 3 to 5 hours. After cooling naturally, the original powder of the CoCrNi / TiC medium-entropy alloy is obtained.
[0019] Preferably, S2 comprises the following steps:
[0020] S2.1. Calculate the mass of TiC powder and CoCrNi powder required for the corresponding atomic ratio, weigh them with a precision balance and put them into a ball mill for use. The volume of powder in each ball mill should not exceed 1 / 3-1 / 2 of the ball mill.
[0021] S2.2, fix the ball milling jar in S2.1 in the ball mill, use the speed of 250-300r / min to carry out ball milling, the ball milling time is 2-4 hours, and put the powder after each ball milling into a vacuum glass drying dish for standby use;
[0022] S2.3, put the ball-milled powder obtained in S2.2 into a vacuum drying oven, dry it at 68-72°C for 3-5 hours, and wait for it to slowly cool to room temperature before taking it out for use;
[0023] S2.4, pour the dried powder in S2.3 into the printer and start printing the sample on the substrate;
[0024] S2.5. Cut the sample printed on the substrate in S2.4 by wire cutting for subsequent experiments.
[0025] Preferably, S3 also includes the preparation of CoCrNi / TiC medium entropy alloy by laser additive manufacturing, and the preparation process is:
[0026] S3.1. Place powder with a particle size of (10-60) μm into the powder feeding cylinder of the 3D printing device;
[0027] S3.2. Select the parameters of the 3D printing device and start the 3D printing device;
[0028] S3.3. Under the protection of high concentration argon, laser scanning is performed layer by layer according to the set parameters to form the original powder on the stainless steel substrate until the printing is completed, and the medium-entropy alloy manufactured by laser additive manufacturing can be obtained.
[0029] Preferably, the setting of the 3D printing equipment parameters in S3.2 is specifically as follows:
[0030] Printing method: partition type; filling strategy during printing: straight line; laser power: 150W; scanning speed: 500mm / s; powder thickness: 40μm; scanning spacing: 60μm, laser energy density is 125J; the sample is printed under the protection of inert gas argon, and the oxygen content of the 3D printing equipment during printing must be ≤100ppm.
[0031] Preferably, the 3D printing device performs laser printing layer by layer according to a set program as follows: scanning with laser strips of multiple laser beams, the direction of each layer of laser is the same and parallel to each other, the laser direction is rotated 67° between the first and next times for layer-by-layer scanning, the printed molten pool is 80 μm, and the 304 stainless steel substrate needs to be preheated before printing, and the preheating time and temperature are 1 to 2 hours and 88 to 92° C., respectively.
[0032] The present invention also provides a CoCrNi medium entropy alloy manufactured by TiC ceramic powder reinforced laser additive manufacturing obtained by the method.
[0033] Beneficial effects of the present invention:
[0034] (1) The present invention uses a mechanical ball milling method to evenly mix the two powders to achieve the purpose of strengthening the performance of the CoCrNi medium-entropy alloy; under the premise of low energy consumption, the density and Vickers hardness of the medium-entropy alloy are improved, the average grain size is refined, the dislocation between the grains is hindered, and a CoCrNi medium-entropy alloy with better performance is prepared.
[0035] (2) The present invention also facilitates uniform heat dispersion and reduces cooling time during sample preparation by adding a specific proportion of TiC ceramic powder, thereby making the nanocrystals in the printing molten pool grow evenly and refining the size of the nanocrystals, thereby achieving the purpose of refining the grains and reducing internal defects.
[0036] (3) The present invention sets two alloy powders and forms three alloys; specifically, by powder screening, the parameters of the set 3D printing equipment are selected, and under the protection of high-concentration argon gas, laser scanning is performed layer by layer according to the set parameters, so that the original powder is formed on the stainless steel substrate until the printing is completed, and the medium-entropy alloy manufactured by laser additive manufacturing can be obtained, which ensures that the time and steps for preparing the medium-entropy alloy are reduced, the energy consumption is reduced, and the preparation speed is increased.
[0037] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0039] Figure 1 A schematic flow chart of a method for manufacturing a CoCrNi medium entropy alloy by laser additive manufacturing using TiC ceramic powder according to the present invention;
[0040] Figure 2 The macroscopic morphology and microstructure of the CoCrNi medium entropy alloy manufactured by TiC ceramic powder enhanced laser additive manufacturing of the present invention; wherein (a) is the macroscopic morphology and microstructure of alloy 1, (b) is the front scanning electron microscope image of the macroscopic morphology and microstructure of alloy 2, and (c) is the front scanning electron microscope image of the macroscopic morphology and microstructure of alloy 3;
[0041] Figure 3 This is a front scanning electron microscope image of the medium entropy alloy of alloy 1 of the present invention;
[0042] Figure 4 This is a front scanning electron microscope image of the medium entropy alloy of alloy 2 of the present invention;
[0043] Figure 5 This is a front scanning electron microscope image of the medium entropy alloy of alloy 3 of the present invention;
[0044] Figure 6 This is a microstructure morphology diagram of the molten pool of the medium-entropy alloy of the invention alloy 1;
[0045] Figure 7 is a microstructure morphology diagram of the molten pool of the medium-entropy alloy of the invention alloy 2;
[0046] Figure 8 This is a diagram of the microstructure in the molten pool of the medium-entropy alloy of invention alloy 3. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] See also Figure 1 As shown, the present invention is a method for TiC ceramic powder enhanced laser additive manufacturing CoCrNi medium entropy alloy, the method comprising:
[0049] S1. CoCrNi alloy powder and TiC ceramic powder with particle sizes of (10-60) μm are selected, and the atomic ratio of the two is CoCrNi:TiC=(0.8-1):(0.2-0), for preparing CoCrNi / TiC medium entropy alloy powder;
[0050] S2, preparing a mixed powder of CoCrNi and TiC ceramics by mechanical ball milling;
[0051] S3. The mixed powder is vacuum dried, and a TiC ceramic powder reinforced CoCrNi medium entropy alloy material with few defects and excellent performance is prepared by selective laser melting (SLM).
[0052] Through the above technical scheme: in order to reduce the adverse effects of cracks and shrinkage defects generated by additive manufacturing of CoCrNi medium entropy alloy on parts, as well as the high temperature and long time required in traditional methods for eliminating and reducing defects, the present invention uses a method for laser additive manufacturing of CoCrNi medium entropy alloy, which improves the density and Vickers hardness of the medium entropy alloy under the premise of low energy consumption, hinders dislocation between nanocrystals, and prepares CoCrNi medium entropy alloy with better performance. The present invention also adds a specific proportion of TiC ceramic powder, which is beneficial to uniform heat dispersion during sample preparation, reduces cooling time, and homogenizes nanocrystal growth and refines the size of nanocrystals, thereby achieving the effect of refining grains and reducing internal defects.
[0053] Specifically, firstly, CoCrNi alloy powder and TiC ceramic powder alloy powder are prepared; then, CoCrNi / TiC medium entropy alloy powder is prepared; finally, the two powders are mixed evenly by mechanical ball milling, so as to enhance the performance of CoCrNi / TiC medium entropy alloy.
[0054] As an embodiment of the present invention, specifically, the specific process of the CoCrNi / TiC entropy alloy powder in S1 is:
[0055] S1.1. Weigh the original CoCrNi metal powder and TiC ceramic powder according to the calculated powder mass. The average particle size of the two powders is (10-60) μm. The two alloy powders are in atomic (CoCrNi) y / TiC x It means that x+y=1;
[0056] Among them, (CoCrNi) y / TiC x The atoms included are: Alloy 1: (CoCrNi)1; Alloy 2: CoCrNi 0.9 / TiC 0.1 ; Alloy 3: CoCrNi 0.8 / TiC 0.2 ;
[0057] S1.2, put the powder in S1.1 into a ball mill, and use a ball mill for mechanical ball milling;
[0058] S1.3. Collect the ball-milled powder in S1.2 and put it into a vacuum drying oven for drying at a temperature of 68 to 72° C. for 3 to 5 hours. After cooling naturally, the original powder of the CoCrNi / TiC medium-entropy alloy is obtained.
[0059] According to the above technical scheme: firstly, the original CoCrNi and TiC powders are weighed according to the calculated powder mass, and the average particle size of the two powders is (10-60) μm, wherein the two alloy powders are atomic CoCrNi y / TiC x Indicates that the atomic ratio of the two alloy powders provided by the present invention is: alloy 1: (CoCrNi)1; alloy 2: CoCrNi 0.9 / TiC 0.1 ; Alloy 3: CoCrNi 0.8 / TiC 0.2 ; Then, the powder was placed in a ball mill and mechanically milled using a star-shaped ball mill; finally, the milled powder was collected and placed in a vacuum drying oven for drying the day before printing. The drying temperature was 70°C and the drying time was 4 hours. After it was naturally cooled, the original powder of the CoCrNi / TiC medium-entropy alloy was obtained.
[0060] As an implementation mode of the present invention, specifically, S2 includes the following steps:
[0061] S2.1. Calculate the mass of TiC powder and CoCrNi powder required for the corresponding atomic ratio, weigh them with a precision balance and put them into a ball mill for use. The volume of powder in each ball mill should not exceed 1 / 3-1 / 2 of the ball mill.
[0062] S2.2, fix the ball milling jar in S2.1 in the ball mill, use the speed of 250-300r / min to carry out ball milling, the ball milling time is 2-4 hours, and put the powder after each ball milling into a vacuum glass drying dish for standby use;
[0063] S2.3, put the ball-milled powder obtained in S2.2 into a vacuum drying oven, dry it at 68-72°C for 3-5 hours, and wait for it to slowly cool to room temperature before taking it out for use;
[0064] S2.4, pour the dried powder in S2.3 into the printer and start printing the sample on the substrate;
[0065] S2.5. Cut the sample printed on the substrate in S2.4 by wire cutting for subsequent experiments.
[0066] Through the above technical scheme: in order to enhance the performance of the medium entropy alloy and facilitate the acquisition of CoCrNi / TiC medium entropy alloy powder: first, the masses of TiC powder and CoCrNi powder required for the corresponding atomic ratio are calculated respectively, and the corresponding masses are weighed with a precision balance and placed in a ball mill for standby use, and the volume of powder in each ball mill does not exceed 1 / 3-1 / 2 of the ball mill; then, the ball mill in the previous step is fixed in a star-shaped ball mill, and ball milling is performed at a speed of 250-300r / min for 3 hours, and the powder obtained by each ball milling is placed in a vacuum glass drying dish for standby use; then, the ball milled powder obtained in the previous step is placed in a vacuum drying oven, dried at 70°C for 4 hours, and then taken out for standby after it slowly cools to room temperature; once again, the dried powder in the previous step is poured into the 3D printer, and the sample is printed on the substrate; finally, the sample printed on the substrate in the previous step is cut off by wire cutting to ensure subsequent experiments.
[0067] As an embodiment of the present invention, specifically, S3 also includes the preparation of CoCrNi / TiC medium entropy alloy by laser additive manufacturing, and the preparation process is:
[0068] S3.1. Place the mixed powder with a particle size of (10-60) μm into the powder feeding cylinder of the 3D printing device;
[0069] S3.2. Select the parameters of the 3D printing device and start the 3D printing device;
[0070] S3.3. Under the protection of high concentration argon, laser scanning is performed layer by layer according to the set parameters to form the original powder on the stainless steel substrate until the printing is completed, and the medium-entropy alloy manufactured by laser additive manufacturing can be obtained.
[0071] Through the above technical scheme: first, select powder with an average particle size of (10-60) μm and put it into the powder feeding cylinder of the 3D printing device; then, select the parameters of the 3D printing device and start the 3D printing device; finally, under the protection of high-concentration argon gas, perform laser scanning layer by layer according to the set parameters to form the mixed powder on the stainless steel substrate until the printing is completed, and the medium-entropy alloy manufactured by laser additive manufacturing can be obtained.
[0072] As an implementation of the present invention, specifically, the setting of the 3D printing equipment parameters in S3.2 is specifically:
[0073] Printing method: partition type; filling strategy during printing: straight line; laser power: 150W; scanning speed: 500mm / s; powder thickness: 40μm; scanning spacing: 60μm, laser energy density is 125J; the sample is printed under the protection of inert gas argon, and the oxygen content of the 3D printing equipment during printing must be ≤100ppm.
[0074] As an embodiment of the present invention, specifically, the 3D printing device performs laser printing layer by layer according to a set program: scanning with laser strips of multiple laser beams, the direction of each layer of laser is the same and parallel to each other, the first and next laser directions are rotated 67° for layer-by-layer scanning, the printed molten pool is 80μm, and the 304 stainless steel substrate needs to be pre-processed before printing, and the preheating time and temperature are 1h and 90°C respectively.
[0075] As an embodiment of the present invention, specifically, the ball mill jar in S2.2 is fixed on the ball mill and fixed with a pressure clamp to ensure that the ball mill jar does not loosen during ball milling. During ball milling, the ball milling speed is 250-300r / min, the forward and reverse rotations are 30 minutes each, the intermediate residence time is 2min, and the ball milling time is 3 hours.
[0076] The present invention also provides a TiC ceramic powder-enhanced laser additively manufactured CoCrNi medium-entropy alloy obtained by the above method; the CoCrNi / TiC medium-entropy alloys obtained through the above process are alloy 1, alloy 2, and alloy 3 respectively; and a medium-entropy alloy with high density, low cracks, and high hardness is provided, and the preparation method is the same.
[0077] Through the above technical solution: the embodiment of the present invention uses alloy 1, alloy 2; alloy 3 to perform defect comparison analysis and performance test analysis on Examples 1-3 respectively:
[0078] Table 1: Parameters of implementation cases 1-3 and atomic ratio of TiC
[0079] Example 1 Example 2 Example 3 CoCrNi:TiC atomic ratio 1:0 0.9:0.1 0.8:0.2 Laser power / W 150 150 150 Scanning speed / mm / s 500 500 500
[0080] (1) Defect comparison analysis: First, the parameters of implementation cases 1-3 and the atomic ratio of TiC are set. The atomic ratios of CoCrNi:TiC in implementation cases 1-3 are 1:0; 0.9:0.1; 0.8:0.2 respectively; the laser power is set to be the same: 150W; 150W; 150W; the scanning speed is consistent: 500mm / s; 500mm / s; 500mm / s. Then the crack and hole defects are observed and compared, please refer to Figure 2As shown in (a)(b)(c): Through microstructure observation and comparison, alloy 3 (Figure (c) has the least cracks and holes, indicating that the alloy has better printing performance at this TiC atomic ratio. On the other hand, alloy 1, when no TiC ceramic powder is added, has significantly more shrinkage cavities than alloys 2 and 3, which also shows that adding TiC ceramic powder has the effect of reducing defects such as cracks and holes.
[0081] Figure 3 , Figure 4 , Figure 5 The front SEM images of medium entropy alloys with defects such as low porosity are shown in Figure 2. From the front morphology, the three alloys have a "fish scale-like" molten pool. Figure 6 , Figure 7 , Figure 8 It can be seen that there are columnar nanocrystals and cellular nanocrystals inside the molten pool. These nanocrystals are also the fundamental reason why the alloy has good performance and low crack shrinkage defects. With the addition of TiC ceramic powder, the number of columnar nanocrystals in the alloy decreases and the number of cellular nanocrystals increases, which makes these nanocrystals also the fundamental reason why the alloy has good performance and low crack shrinkage defects.
[0082] (2) Performance test: The above embodiment passed the following performance test:
[0083] a. Hardness: After the sample surface is polished with SiC sandpaper, a Vickers microhardness tester is used to measure the average value of the data of more than 5 samples at a load of 200 gf for 15 s.
[0084] Table 3: Hardness data of the examples
[0085] TiC atomic ratio Vickers hardness / HV Example 1 0 287.344 Example 2 0.1 409.255 Example 3 0.2 485.998
[0086] From Examples 1 to 3, it can be seen that the hardness of the alloy is significantly improved by adding TiC ceramic powder.
[0087] b. Density: The sample surface was polished smooth with SiC sandpaper, and the density of the alloy was measured by the water displacement method. Five data were measured for each sample and the average value was taken.
[0088] Table 4 is the density data of the embodiment
[0089] TiC atomic ratio Density Example 1 0 99.07 Example 2 0.1 99.24 Example 3 0.2 99.78
[0090] From the examples, the density of the alloy is also improved by adding TiC ceramic powder, which is also a significant reason why the alloy has good performance, low shrinkage cracks and improved hardness.
[0091] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing, characterized in that: The method comprises: S1. CoCrNi alloy powder and TiC ceramic powder with a particle size of (10~60) μm are selected, and the atomic ratio of the two is CoCrNi:TiC=(0.8~0.9):(0.2~0.1), which are used to prepare CoCrNi / TiC medium entropy alloy powder; S2, preparing a mixed powder of CoCrNi and TiC ceramics by mechanical ball milling; S3. The mixed powder is vacuum dried, and a TiC ceramic powder reinforced CoCrNi medium entropy alloy material with few defects and excellent performance is prepared by selective laser melting (SLM).
2. The method for manufacturing CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing according to claim 1, characterized in that: The specific process of preparing the CoCrNi / TiC medium entropy alloy powder in S1 is: S1.
1. According to the calculated powder mass, weigh the original alloy powder CoCrNi metal powder and TiC ceramic powder with a raw material purity of ≥99.9%. The particle size of the two powders is (10~60) μm. The two alloy powders are atomic (CoCrNi) y / TiC x It means that x+y=1; Among them, CoCrNi / TiC X The atomic ratios are: Alloy 1: (CoCrNi) 1; Alloy 2: (CoCrNi) 0.9 / TiC 0.1 ; Alloy 3: (CoCrNi) 0.8 / TiC 0.2 ; S1.2, put the powder in S1.1 into a ball mill, and use a ball mill for mechanical ball milling; S1.
3. Collect the ball-milled powder in S1.2 and put it into a vacuum drying oven for drying at a temperature of 68-72°C for 3-5 hours. After cooling naturally, the original powder of the CoCrNi / TiC medium-entropy alloy is obtained.
3. The method for manufacturing CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing according to claim 1, characterized in that: The S2 comprises the following steps: S2.
1. Calculate the mass of TiC powder and CoCrNi powder required for the corresponding atomic ratio, weigh them with a precision balance and put them into a ball mill for use. The volume of powder in each ball mill should not exceed 1 / 3-1 / 2 of the ball mill. S2.2, fix the ball milling jar in S2.1 in the ball mill, use the speed of 250-300r / min for ball milling, the ball milling time is 2-4 hours, and put the powder after each ball milling into a vacuum glass drying dish for standby use; S2.3, put the ball-milled powder obtained in S2.2 into a vacuum drying oven, dry it at 68-72°C for 3-5 hours, and wait for it to slowly cool to room temperature before taking it out for use; S2.4, pour the dried powder in S2.3 into the printer and start printing the sample on the substrate; S2.
5. Cut the sample printed on the substrate in S2.4 by wire cutting for subsequent experiments.
4. The method for manufacturing CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing according to claim 3, characterized in that: S3 also includes the preparation of CoCrNi / TiC medium entropy alloy by laser additive manufacturing, and the preparation process is: S3.
1. Place powder with a particle size of (10-60) μm into the powder feeding cylinder of the 3D printing device; S3.
2. Select the parameters of the 3D printing device and start the 3D printing device; S3.
3. Under the protection of high concentration argon, laser scanning is performed layer by layer according to the set parameters to form the original powder on the stainless steel substrate until the printing is completed, and the medium-entropy alloy manufactured by laser additive manufacturing can be obtained.
5. The method for manufacturing CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing according to claim 4, characterized in that: The specific setting of the 3D printing equipment parameters in S3.2 is: Printing method: partition type; filling strategy during printing: straight line; laser power: 150W; scanning speed: 500mm / s; powder thickness: 40μm; scanning spacing: 60μm, laser energy density is 125J; the sample is printed under the protection of inert gas argon, and the oxygen content of the 3D printing equipment during printing must be ≤100ppm.
6. The method for manufacturing CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing according to claim 5, characterized in that: The 3D printing device performs laser printing layer by layer according to the set program: scanning with laser strips of multiple laser beams, the direction of each layer of laser is the same and parallel to each other, the first and next laser directions are rotated 67° for layer-by-layer scanning, the printed molten pool is 80μm, and the 304 stainless steel substrate needs to be preheated before printing, and the preheating time and temperature are 1~2h and 88~92℃ respectively.
7. The method for manufacturing CoCrNi medium entropy alloy by TiC ceramic powder enhanced laser additive manufacturing according to claim 2, characterized in that: The ball milling jar in S2.1 is fixed on the ball mill and fixed with a pressure clamp to ensure that the ball milling jar does not loosen during ball milling. During ball milling, the ball milling speed is 250-300r / min, the forward and reverse rotations are 30 minutes each, the intermediate residence time is 2min, and the ball milling time is 2~4 hours.
8. A laser additively manufactured CoCrNi / TiC medium entropy alloy material obtained by the method for manufacturing CoCrNi medium entropy alloy by laser additively manufacturing TiC ceramic powder according to any one of claims 1 to 7.
Citation Information
Patent Citations
SLM CoCrNi alloy reinforced based on grain boundary segregation and preparation method of SLM CoCrNi alloy
CN114351029A
Cited By
Nanometer TiB2 reinforced CoCrNi medium-entropy alloy and preparation method thereof
CN120382148A
Large-density-difference ceramic particle reinforced medium-entropy alloy powder as well as preparation method and application thereof
CN121360813A